Interpreting Emotions From Women With Covered Faces: A Comparison Between a Middle Eastern and Western-European Sample - Kret, Mariska E.; Maitner, Angela T.; Fischer, Agneta H. (Frontiers in Psychology, 2021)
While new regulations obligate or recommend people to wear medical masks at public places to prevent further spread of the Covid-19 virus, there are still open questions as to what face coverage does to social emotional communication. Previous research on the effects of wearing veils or face-covering niqabs showed that covering of the mouth led to the attribution of negative emotions and to the perception of less intense positive emotions. The current study compares a sample from the Netherlands with a sample from the United Arab Emirates on their perception of emotions from faces covered by a niqab, censoring black bars, or uncovered faces. The results show that covering the mouth area leads to greater anxiety in participants in both countries. Furthermore, although participants did not report greater decoding difficulties for faces that were covered as compared to fully visible, results show that face coverage did influence emotion perception. Specifically, happiness and anger were perceived as being less intense. Further, face coverage by a niqab, as compared to black bars, yielded lower emotional intensity ratings. We conclude that face coverage in particular can modulate the perception of emotions, but that affective contextual cues may play a role as well.